Application of QPSK-OFDM for Improved Underwater Wireless Communication System - Elechi, P.; Kukuchuku, S.; Egwaile, J.O. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
The problems of signal loss and poor channel estimation are inherent in underwater communication. In this work, underwater communication system has been improved using Orthogonal Frequency Division Multiplexing (OFDM) system with quadrature phase shift keying (QPSK) based on modulation scheme. The modern choice of underwater communication system, where the available bandwidth was divided into many overlapping sub-channels, such that the symbol duration was compared to the multipath spread of the channel; thus, eliminating inter symbol interference as well as improving bandwidth availability. Matlab tool was used to develop and implement series of simulations of the underwater acoustic communication system model. The proposed OFDMQPSK underwater wireless acoustic technique achieved a BER of 2.44 ×